Amphibian and reptile diversity of Peleng Island, Banggai Kepulauan, Central Sulawesi, Indonesia - AWAL RIYANTO; CAHYO RAHMADI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Riyanto A, Rahmadi C. 2021. Amphibian and reptile diversity of Peleng Island, Banggai Kepulauan, Central Sulawesi, Indonesia. Biodiversitas 22: 2930-2939. Indonesia is an archipelagic country and is known as one of the world’s megadiverse countries and has three zoogeographic zones. Therefore, proper conservation efforts to face extinction threats are very important, and the fundamental steps to better understanding it’s biodiversity provide valuable baseline information. Amphibians and reptiles (herpetofauna) are main biodiversity components that experience extinction threats but, at the same time, provide an important role in ecosystems and community life. This paper is the first to provide a checklist of the herpetofauna of Peleng Island, Banggai Kepulauan, Central Sulawesi, Indonesia. Data was gathered by field surveys and supplemented by references. Visual Encounter Surveys (VES) were undertaken in 8 sites. A total of 34 species are listed herein, 29 (85%) of them revealed from this fieldwork, and 21 (62%) new for the island. At least two candidate new species of the genus Cyrtodactylus were confirmed by molecular data and one frog of the genus Kaloula also suspected new species.